1997
DOI: 10.1128/mcb.17.1.209
|View full text |Cite
|
Sign up to set email alerts
|

Postfertilization Deadenylation of mRNAs in Xenopus laevis Embryos Is Sufficient To Cause Their Degradation at the Blastula Stage

Abstract: Although the maternal Xenopus laevis Eg mRNAs are deadenylated after fertilization, they are not immediately degraded and they persist in the embryos as poly(A) ؊ transcripts. The degradation of these RNAs is not detected until the blastula stage of development (6 to 7 h postfertilization). To understand the basis for this delay between deadenylation and degradation, it is necessary to identify the cis-acting element(s) required to trigger degradation in blastula stage embryos. To this end, several chimeric RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 26 publications
5
85
0
Order By: Relevance
“…A completely deadenylated form of the GbORF-jun transcript could be detected as early as 1 h after injection (lane 6), and the transcript was predominantly deadenylated 3 h after injection (lane 8). In contrast, and as previously shown (12), no completely deadenylated form of the reporter RNA alone (GbORF) could be detected, even 3 h after injection (lane 4). The deadenylation pattern of the GbORF transcript is evocative of default deadenylation, a slow activity for which the only sequence specificity is an absence of a CPE, which is stimulated during oocyte maturation and persists after fertilization (23)(24)(25).…”
Section: C-jun Are Provokes Rapid Deadenylation Of a Reporter Rna In mentioning
confidence: 44%
See 2 more Smart Citations
“…A completely deadenylated form of the GbORF-jun transcript could be detected as early as 1 h after injection (lane 6), and the transcript was predominantly deadenylated 3 h after injection (lane 8). In contrast, and as previously shown (12), no completely deadenylated form of the reporter RNA alone (GbORF) could be detected, even 3 h after injection (lane 4). The deadenylation pattern of the GbORF transcript is evocative of default deadenylation, a slow activity for which the only sequence specificity is an absence of a CPE, which is stimulated during oocyte maturation and persists after fertilization (23)(24)(25).…”
Section: C-jun Are Provokes Rapid Deadenylation Of a Reporter Rna In mentioning
confidence: 44%
“…Cloning Procedures-c-Jun ARE (4, 21) was amplified by RT-PCR from HeLa cell RNA with the following primers: sense, GCTCTAGAT-CTGGCCTGCTTTCGTTAACTGTGTATG; antisense, GTAATGGATC-CTCTTTTTATTAGGAGCAGATACGCTAGCTTTATTAAATCTCTTAT-TTACAAACAACACTGGGC and was cloned into the BamHI and XbaI sites of the pGbORF vector (12), giving the pGbORF-jun plasmid. Annealed primers sense, CTAGAAGCTTAGATCTATTTATTTATTTA-TTTATTTATTTATTTATTTACTAGTGGTACC; antisense, CTAGGTA-CCACTAGTAAATAAATAAATAAATAAATAAATAAATAAATAGATC-TAAGCTT were cloned in the XbaI and NheI sites of the same vector to give the pGBORF-AUUUA plasmid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Purification of Xenopus PARN+ A: A total of 2+5 mg total protein from S100, DEAE, and heparin active fractions and 50 units xPARN activity from the active poly(A) fraction were resolved by SDS-PAGE (15%) and detected by silver staining+ B: Fractionation of the active poly(A) material by MonoQ chromatography+ Proteins were resolved by SDS-PAGE (15%) and detected by silver staining+ The graph below indicates the amount of xPARN activity in corresponding fractions+ suggesting that p62 is derived from the p74 species by proteolytic cleavage+ This appears to be a specific cleavage, as the truncated p62 protein is not further degraded+ In addition, this proteolysis appears to be insensitive to PMSF, which was used throughout the purification+ Interestingly, the putative modification of p74 is also lost in the absence of protease inhibitors+ These data indicate that p74 is the precursor of p62 and, because the activity of p74 hPARN is stimulated by the presence of a 59 cap, we believe that p74 xPARN is responsible for cap-dependent activity observed in mature Xenopus oocytes in vivo+ Previous analysis of xPARN subcellular localization showed that p62 is cytoplasmic whereas p74 is nuclear (Korner et al+, 1998)+ Analyses of the predicted protein sequence of xPARN using the PORT II Prediction algorithm reveals the presence of a single putative nuclear localization signal (NLS) located in the C-terminal portion (amino acids 522-539)+ Thus, it is likely that the proteolysis is occurring in the C-terminal domain and that this region is required for nuclear localization+ Figure 2C shows a developmental western blot probed with anti-hPARN and FRGY2 antibodies as described above+ This blot shows that p74 xPARN protein is readily detectable in later embryonic stages with an apparent peak of expression during gastrulation+ These data suggest that xPARN activity persists well after fertilization and therefore may also participate in fertilization-specific deadenylation (Bouvet et al+, 1994;Sheets et al+, 1994;Stebbins-Boaz & Richter, 1994;Legagneux et al+, 1995) as well as post-mid-blastula transition mRNA destabilization (Audic et al+, 1997;Voeltz & Steitz, 1998)+…”
Section: Purification Of Parn From Xenopus Oocytesmentioning
confidence: 98%
“…Interestingly, there is no decay of Xenopus messages following deadenylation through oocyte maturation or in the early stages of embryo development (until the mid-blastula transition), suggesting a reversible regulatory process that can shift mRNAs between repressed and translationally active states (Audic et al 1997;Voeltz and Steitz 1998). Tethering of poly(A) polymerase leads to premature activation of translation of such messages (Dickson et al 2001;Rouhana et al 2005).…”
Section: Poly(a)-dependent Translation Controlmentioning
confidence: 99%